Copper Salt of 12‐Tungstophosphoric Acid: An Efficient and Reusable Heteropoly Acid for the Click Chemistry. Issue 4 (1st March 2013) - Purnima, K. V.; Sreenu, D.; Bhasker, N.; Nagaiah, K.; Lingaiah, N.; Subba Reddy, B. V.; Yadav, J. S.
Abstract Three components coupling of alkyl bromide, sodium azide and alkyne has been achieved using a catalytic amount of copper‐exchanged phosphotungstic acid (Cu‐TPA) in the presence of triethyl amine in DMF to afford substituted triazoles in good yields with high selectivity. Interestingly, the coupling of alkyl azide with alkyne proceeds readily at room temperature to furnish 1, 2, 3‐triazoles in excellent yields. The catalyst can be recovered and reused for three to four subsequent runs with a minimal decrease of activity. The use of copper modified heteropolyacids makes this procedure simple, convenient and environmentally friendly.